Vaccination campaign at a temporary camp for victims of the earthquake in Lorca (Spain) - Jaime Jesús Pérez-Martín; Francisco José Romera Guirado; Yolanda Molina-Salas; Pedro José Bernal-González; José Antonio Navarro-Alonso (Taylor & Francis Group, 2017)
Outbreaks in temporary camps are an important risk for the health of the displaced population. The town of Lorca (Murcia, Spain) suffered 2 earthquakes on May 2011 that required the re-housing of 1,424 victims in a temporary camp. Following 4 cases of chickenpox control measures were adopted among the displaced population. These measures included vaccination against chickenpox; due to the existence of cases of measles in adjacent regions, it was decided to offer measles, mumps and rubella (MMR) vaccination as well. The immunization campaign was performed during 2 d (3 to 4 d after the first case). The immunity status of 1,041 (73,1%) of the residents was reviewed. Being vaccinated 523 (67%) against chickenpox and MMR, 133 (17%) against only MMR and 124 (16%) against only chickenpox. We consider the action taken was a success, as only 4 additional cases of chickenpox were subsequently recorded in the campsite, being avoidable only one of them. There is a major risk of outbreaks in a disaster situation. Because of this, conducting preventive actions are indicated to avoid doing worse this critical.